Garland in His Own Time : A Biographical Chronicle of His Life, Drawn from Recollections, Interviews, and Memoirs by Family, Friends, and Associates - Newlin, Keith (Writers in their own time., 2013)
In his heyday, Hamlin Garland had a considerable reputation as a radical writer whose realistic stories and polemical essays agitating for a literature that accurately represented American life riled the nation's press. The sixty-six reminiscences in Garland in His Own Time offer an essential complement to his self-portrait by giving the perspectives of family, friends, fellow writers, and critics. The book offers the contemporary reader new reasons to return to this fascinating writer's work.